PENERAPAN MODEL PEMBELAJARAN ARIAS BERBANTUAN MEDIA QUIZIZZ UNTUK MENINGKATKAN MOTIVASI BELAJAR APLIKASI PENGOLAH ANGKA - Astina Damayanti; siswandari siswandari; nurhasan hamidi (Universitas Sebelas Maret, 2021)
AbstractThe aim of this study is to improve motivation of learning spreadsheet through the application of the Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) learning model assisted by Quizizz media on students of SMK. This study is classroom action research. The subjects of this study were students of class X Accounting at SMK, including 36 students. The data collection technique used in this study was observation, documentation, and questionnaires. Content validity is used to test the validity of the resulting data. The data analysis technique used in this study was qualitative and quantitative descriptive analysis techniques. This study was conducted in two cycles consisting of planning, implementing, observing, and reflecting. The results showed that the application of the ARIAS learning model assisted by the Quizizz media could increase the spreadsheets’ learning motivation of grade X Accounting students at SMK. Increased motivation to learn occurs in each indicator. Increased motivation to learn occurs in each indicator. The average score of students' learning motivation increased by 55 points (from 64 to 119) in the cycle II. This increase is statistically significant with t count 28.848> t table 2.030 (p-value = 0.000) at α = 0.05. Keyword: Learning Motivation, ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction), Quizizz.AbstrakTujuan penelitian ini untuk meningkatkan motivasi belajar aplikasi pengolah angka melalui penerapan model pembelajaran Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) berbantuan media Quizizz pada siswa SMK. Penelitian ini merupakan penelitian tindakan kelas. Subjek dari penelitian ini adalah siswa kelas X Akuntansi di SMK yang berjumlah 36 siswa. Teknik pengumpulan data yang digunakan adalah teknik observasi, dokumentasi, dan angket. Validitas isi digunakan untuk menguji validitas data yang dihasilkan. Teknik analisis data menggunakan teknik analisis deskriptif kualitatif dan kuantitatif. Penelitian dilaksanakan dalam dua siklus yang terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi . Hasil penelitian menunjukkan bahwa penerapan model pembelajaran ARIAS berbantuan media Quizizz dapat meningkatkan motivasi belajar aplikasi pengolah angka siswa kelas X Akuntansi di SMK. Peningkatan motivasi belajar terjadi pada tiap indikator. Rata-rata skor motivasi belajar siswa meningkat 55 poin (dari 64 menjadi 119) pada siklus II . Peningkatan ini signifikan secara statistik dengan t hitung 28,848 > t table 2,030 (p-value = 0,000) pada α= 0,05. Kata kunci: Motivasi Belajar, ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction), Quizizz.